interfaces da intolerância religiosa na educação para a diversidade sexual na Rede Municipal de ensino do Recife. - Gouveia, Regina Bezerra de (2018)
This resarch aims to reflect the representative interface about the connections between sexual and religion, as weel as to investigate the social representations of Recife Municipal Education Network – RMER – teachers, with religious identities, around the Recife. We chose the Theory of Social Representations of Moscovici (2003) to understand the meanings shared by teachers about Sexual Diversity form the implementation of the Education Policy of Recife. We use Content Analysis, by Bardin (2011), to analyze and interpret the data in the apprenhension of responses that present possible directions for harmonizing the recurring conflicts between religion and the affirmative education of plural identities, differences and LGBT rights. The analysis of the data revealed that RS harbor contradictions and inconsistencies, in the face of sexual diversity and education policy, depending on religious beliefs. Another notable result is the high percentage of teachers who do not know the theoretical basis of Sexuality Education present in Recife's Education Policy. The results that point out some ways to solve the conflicts point out that answers from the perspective of social, human and plural need to come as much through the educational, academic and social, as through the religious way.